Multi-level governance the missing linkages - Ongaro, Edoardo (Bingley, U.K. : Emerald, 2015)
Multi-level governance (MLG) is a highly influential, supple and ductile framework for interpreting governance in complex polities. Yet, criticisms have been aimed at its allegedly overly "descriptive", rather than explanatory, power. This volume argues that progress in both the study and the practice of MLG may derive from developing linkages with disciplines, perspectives and issues that have so far not been explored in connection to MLG. By discussing cases ranging from nuclear power policy to environmental policy in both the Western world and in Eastern Asia, and by engaging different theoretical perspectives and issues of practical significance, such as legitimacy in public decisions or the management of risk in multi-level settings, the book proposes ways forward for advancing the understanding of MLG - a framework of reference in the analysis of contemporary governance. The book will provide scholars and students in the fields of public administration, public policy and political science with key concepts for the analysis of contemporary governance issues, and will be a source of ideas for practitioners and policy-makers engaged in making public decisions in complex polities.
Multi-level governance : the missing linkages / Edoardo Ongaro -- Multi-level governance, EU public policy, and the evasive dependent variable / Anthony R. Zito -- Revisiting the management deficit : can the Commission (still not) manage Europe? / Hussein Kassim -- The independent EU commissioner : an administrative analysis / Adriaan Schout, Arnout Mijs -- EU agencies and the European multi-level administrative system / Edoardo Ongaro ... [et al.] -- The interaction between agencies, networks and the European Commission in emerging regulatory constellations : a comparative analysis of the European telecom sector and the European patent system / Esther van Zimmeren, Emmanuelle Mathieu, Koen Verhoest -- Multi-level governance, the EU and civil society : a missing link? / Simone Baglioni -- Administrative reforms in the intergovernmental setting : impacts on multi-level governance from a comparative perspective / Sabine Kuhlmann -- Bridging the gaps in multi-level governance : new spaces of interactions and multiple accountabilities in English sub-national governance / Joyce Liddle -- Metagovernance, risk and nuclear power in Britain / Keith Baker -- Politics and political strategies in multi-level systems / Duncan McTavish -- Multi-level governance of hydropower in China? The problem of transplanting a western concept into the Chinese governance context / Oliver Hensengerth -- Multi-level governance : underplayed features, overblown expectation, and missing linkages / Simona Piattoni.
Print version record
Keywords: Political Science -- Public Affairs & Administration; Public administration; Decentralization in government -- European Union countries; Regionalism -- European Union countries; Central-local government relations -- European Union countries